Monocyte and T Cell Immune Phenotypic Profiles Associated With Age Advancement Differ Between People With HIV, Lifestyle-Comparable Controls and Blood Donors - De Francesco, Davide; Sabin, Caroline A.; Reiss, Peter; Kootstra, Neeltje A. (Frontiers in Immunology, 2020)
Motivation: People with HIV on successful antiretroviral therapy show signs of premature aging and are reported to have higher rates of age-associated comorbidities. HIV-associated immune dysfunction and inflammation have been suggested to contribute to this age advancement and increased risk of comorbidities. Method: Partial least squares regression (PLSR) was used to explore associations between biological age advancement and immunological changes in the T cell and monocyte compartment in people with HIV (n=40), comparable HIV-negative individuals (n=40) participating in the Comorbidity in Relation to AIDS (COBRA) cohort, and blood donors (n=35). Results: We observed that age advancement in all three groups combined was associated with a monocyte immune phenotypic profile related to inflammation and a T cell immune phenotypic associated with immune senescence and chronic antigen exposure. Interestingly, a unique monocyte and T cell immune phenotypic profile predictive for age advancement was found within each group. An inflammatory monocyte immune phenotypic profile associated with age advancement in HIV-negative individuals, while the monocyte profile in blood donors and people with HIV was more reflective of loss of function. The T cell immune phenotypic profile in blood donors was related to loss of T cell function, whereas the same set of markers were related to chronic antigen stimulation and immune senescence in HIV-negative individuals. In people with HIV, age advancement was related to changes in the CD4+ T cell compartment and more reflective of immune recovery after cART treatment. Impact: The identified monocyte and T cell immune phenotypic profiles that were associated with age advancement, were strongly related to inflammation, chronic antigen exposure and immune senescence. While the monocyte and T cell immune phenotypic profile within the HIV-negative individuals reflected those observed in the combined three groups, a distinct profile related to immune dysfunction, was observed within blood donors and people with HIV. These data suggest that varying exposures to lifestyle and infection-related factors may be associated with specific changes in the innate and adaptive immune system, that all contribute to age advancement.